WASHINGTON AND LATIN AMERICA: A CONSIDERABLE INDIFFERENCE (2016)
This paper offers an analysis of historical, political, economic, and social events on which US-Latin American relations have been based. Centered on a constructivist approach, I review the main stages for explaining the quality and intensity of the interaction between the actors under consideration. In addition, I contend that US-Latin American relations have been cyclical in nature, and that these cycles have in turn complicated the task of assessing the dynamic of the relationship over the long term.I argue that the US achieved economic and political control over Latin America from the Nineteenth century. Although the specific circumstances that governed US-Latin American relations changed throughout the Twentieth century, this basic condition of domination remained. The situation changed, however, at the beginning of the Twenty-First century, during which Washington effectively lost Latin America. Nonetheless, Washington and Latin America are currently experiencing a rapprochement. This paper explains this sequence in detail and opens new discussions.